Sustainment of a patient flow intervention in an intensive care unit in a regional hospital in Australia: a mixed-method, 5-year follow-up study. Issue 6 (22nd June 2021) - Ros, Eva; Ros, Axel; Austin, Elizabeth E; De Geer, Lina; Lane, Paul; Johnson, Andrew; Clay-Williams, Robyn
Abstract : Objective: In 2014, an escalation plan and morning handover meetings were implemented in an intensive care unit (ICU) to reduce access block for post-operative care. In this study, the improvement intervention is revisited 5 years on with the objective to see if the changes are sustained and to understand factors contributing to sustainability. Design: A mixed-method approach was used, with quantitative analysis of ICU administrative data and qualitative analysis of interviews with hospital management and ICU staff. Setting: ICU with mixed surgical and non-surgical cases in a regional hospital in Australia. Participants: Interview participants: ICU nurses (four), ICU doctors (four) and hospital management (four). Main outcome measures: Monthly number of elective surgeries were cancelled due to unavailability of ICU beds. Staff perceptions of the interventions and factors contributed to sustainability. Results: After a decline in elective surgeries being cancelled in the first year after the intervention, there was an increase in cancellations in the following years (χ 2 =16.38, p=0.003). Lack of knowledge about the intervention and competitive interests in the management of patient flow were believed to be obstacles for sustained effects of the original intervention. So were communication deficiencies that were reported within the ICU and between ICU and other departments. There are discrepancies between how nurses and doctors use the escalation plan and regard the availability of ICU beds. Conclusion: Improvement interventions in healthcare that appear initially to be successful are not necessarily sustained over time, as was the case in this study. In healthcare, there is no such thing as a 'fix and forget' solution for interventions. Management commitment to support communication within and between microsystems, and to support healthcare staff understanding of the underlying reasons for intervention, are important implications for change and change management across healthcare systems.